2009
DOI: 10.1007/s11547-009-0455-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of 64-MDCT and 1.5-T MRI with highresolution sequences in the T staging of gastric cancer: a comparative analysis with histopathology

Abstract: MR imaging and 64-MDCT accuracy levels did not differ in advanced stages of disease, whereas MR imaging was superior in identifying early stages of gastric cancer and can be considered a valid alternative to MDCT in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 36 publications
0
33
0
7
Order By: Relevance
“…The literature yields accuracy values ranging from 69 to 89 % for MDCT and from 73.5 to 87.5 % for MRI along with an accuracy of 76.7 % for EUS and 78.2 % for MDCT, respectively, without significant differences [16,33]. In our study EUS showed the highest sensitivity, underlining the primary role of this technique in the detection of locally advanced tumours and, thus, its capability to correctly recommend neoadjuvant therapy instead of immediate surgical resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature yields accuracy values ranging from 69 to 89 % for MDCT and from 73.5 to 87.5 % for MRI along with an accuracy of 76.7 % for EUS and 78.2 % for MDCT, respectively, without significant differences [16,33]. In our study EUS showed the highest sensitivity, underlining the primary role of this technique in the detection of locally advanced tumours and, thus, its capability to correctly recommend neoadjuvant therapy instead of immediate surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…breath-hold sequences and diffusion-weighted imaging (DWI)] have improved the value of MRI for abdominal imaging, including imaging of gastric cancer [16]; in particular, on DWI pathological tissue is characterized by higher signal intensity than normal structures [17]. MRI studies report an accuracy ranging from 73.5 to 87.5 % for T stage [18,19] and from 55.2 to 65 % for N stage [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that exist mostly compare multislice CT with MRI. These studies did not show a substantial benefit of one over the other method (Anzidei et al 2009;Wang et al 2000). The same was found for the staging of regional lymph nodes.…”
Section: Mrimentioning
confidence: 51%
“…We compared the pooled T (T3-4 vs T1-2) performance characteristics of MRI with DWI 9,22,24,25 to those without DWI 23,[26][27][28][29][30] to determine whether DWI could have helped preoperative staging performances (Table 4). However, we found that the summary results for T staging of GC (Table 4) showed no statistically significant difference between MRI with DWI and without DWI in sensitivity (p 5 0.279) and specificity (p 5 0.283).…”
Section: Subgroup Analysesmentioning
confidence: 99%